An Analysis of Psychological Trauma and Depression of Survivors in Recurring Disaster - Suryana, Elvi; Nizamuddin, Nizamuddin; Sabti, Agus; Imran, Imran; Syahrul, Syahrul; Mawarpury, Marty (SCAD Independent, 2020)
The study aimed to determine psychological trauma and depression in survivors of recurring disasters (the 2004 and 2012 earthquakes in Aceh). A quantitative approach was used as the research design, 2 villages located in Banda Aceh were taken as the samples involving 60 respondents from the two villages. The respondents' criteria were: 1) experiencing two earthquakes in 2004 and 2012, 2) aged over 30 years. Data collection used a modification of the Hamilton Anxiety Rating Scale questionnaire, depression scale, and demographic data. The results showed that there was no correlation between psychological trauma and depression in survivors of the recurring earthquake in Aceh. Besides, based on the results of data analysis, there was a correlation between symptoms (p≤0,000), occupation (p≤0,030), and age (p≤0,015) with psychological trauma; and there was no correlation between potential disasters (p≤0,075), family support (p≤0,002), education (p≤0,181) coping ability (p≤0,401), the value of faith (p≤0,266), and income (p≤0,830) with psychological trauma.